The tastes of Xinjiang - Liu, Yan ("Charming Xinjiang" series, 2014)
This book introduces the deep-rooted, distinctive and most representative tastes of Xinjiang in vivid language, from the three aspects of food, fruits and drinks. A large variety of topics are included, ranging from the unique geographical features and impressive ethnic customs through telling about relevant historical legends, classic flavor, all the way to health care efficacy of food.